Incidence and risk factors for dental pathology in patients planned for elective total hip or knee arthroplasty - Vuorinen, M.; Mäkinen, T.; Rantasalo, M.; Leskinen, J.; Välimaa, H.; Huotari, K. (Scandinavian journal of surgery, 2019)
Background and Aims: To prevent severe prosthetic joint infections, a dental examination is usually recommended prior to arthroplasty, even sometimes regarded resource- and time-consuming. The aim of this study was to determine whether a risk factor-based algorithm could be created to send only selected patients for dental clearance. Materials and Methods: A prospective study of 952 patients scheduled for elective arthroplasty was performed. Patients filled out a questionnaire regarding potential risk factors for dental infections, and dentists documented patients’ oral health and interventions performed (data available for 731 patients). Results: Of the patients, 215 (29.4%) failed dental clearance; a total of 432 teeth were extracted, 32 patients (4.4%) required root canal treatment, and 37 patients (5.1%) had severe periodontitis. Independent risk factors for failure were history of root canal treatment (odds ratio: 2.282, 95% confidence interval: 1.346–3.869, p = 0.020), use of tobacco products (odds ratio: 1.704, 95% confidence interval: 1.033–2.810, p = 0.037), dental visit indicated by oral symptoms within 3 months (odds ratio: 1.828, 95% confidence interval: 1.183–2.827, p = 0.007), or visit to a dentist within 6 months (odds ratio: 1.538, 95% confidence interval: 1.063–2.224, p = 0.022). Regular dental examination was a preventive factor (odds ratio: 0.519, 95% confidence interval: 0.349–0.773, p = 0.001). However, based on the examined risk factors, no sufficiently large group of patients at lesser risk for dental infections could be identified. Conclusion: Because of the high need for dental care revealed by our unselected patient population, the inspection and treatment of dental pathology of all patients are important interventions prior to elective arthroplasty.